Peranan Audit Internal Dalam Menunjang Efektivitas Penyusunan Laporan Keuangan pada PT. Bank Syariah Indonesia - Wahyuni, Wahyuni; Badollahi, Ismail; Nurhidayah, Nurhidayah; Mahfiza, Mahfiza; Nurdiana , Nurdiana (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
This research is to find out the role of internal audit in supporting the effectiveness of preparing financial reports at PT. Indonesian Sharia Bank. This type of research uses descriptive qualitative. Informants taken by internal auditors, BOSM and Tellers at PT. Indonesian Sharia Bank. The research stages are in-depth interviews and observation. The data analysis method is qualitative descriptive research and quantitative descriptive research.The results of this research indicate that the role of internal audit in supporting the effectiveness of preparing financial reports using the interview method with auditors, BOSM and PT Tellers. Indonesian Sharia Bank has been very effective. This is demonstrated in the role of internal audit as supervisor, consultant, catalyst and effectiveness so that it can provide information that helps managerial parties in making decisions.